2013
DOI: 10.1093/cid/cit753
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium Chelonae Infections Associated With Bee Venom Acupuncture

Abstract: We report 3 cases of Mycobacterium chelonae infections after bee venom acupuncture. All were treated with antibiotics and surgery. Mycobacterium chelonae infections should be included in the differential diagnosis of chronic skin and soft tissue infections following bee venom acupuncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
1
4
0
2
Order By: Relevance
“…A combination antimicrobial therapy is however recommended to avoid development of mutational resistance. Moxifloxacin has proven to be a successful supplement to clarithromycin in this case as well as in other case reports 24. A minimum of 4 months is necessary to treat skin or soft tissue infection.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…A combination antimicrobial therapy is however recommended to avoid development of mutational resistance. Moxifloxacin has proven to be a successful supplement to clarithromycin in this case as well as in other case reports 24. A minimum of 4 months is necessary to treat skin or soft tissue infection.…”
Section: Discussionsupporting
confidence: 59%
“…While M. fortuitum causes infection primarily by direct inoculation, M. chelonae often causes infection in immunosuppressed patients. M. chelonae infection should be considered in patients with chronic soft tissue infections non-responsive to commonly used antimicrobial therapies 24. The source of M. chelonae infection is usually not identified due to the ubiquitous presence in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most species are nonpathogenic, Thomson et al found pathogenic NTM species in large urban water distribution systems in Australia [ 4 ]. Human NTM diseases (e.g., pulmonary diseases, lymphadenitis, skin and soft tissue infections, and disseminated diseases) are believed to result from environmental exposure, trauma, and surgical or cosmetic procedures [ 5 ]. In 2019, Hung et al reported a cluster of patients with postoperative M. abscessus endophthalmitis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infections with non-tuberculous mycobacteria have been described increasingly, especially in immunocompromised patients and as iatrogenic infections in immunocompetent patients, causing a variety of local and disseminated disease. RGM in particular can cause local skin and soft tissue infections (SSTI) and have also been described in outbreak and pseudo-outbreak settings involving infections after surgery or other invasive procedures [ 1 ]-[ 3 ]. Here, we describe a case from the Hospital of Tropical Diseases in Ho Chi Minh City, Vietnam of M. fortuitum infection of the skin and soft tissues covering several joints after injection of traditional Vietnamese medicine to relieve joint pain.…”
Section: Introductionmentioning
confidence: 99%